Technological Risk Assessment Process For Technological Risks Petrol And Diesel Supply Chain Activities - Choong, Chien Khay (2020)
The downstream supply chain activities of petroleum are conducting value added activities on crude oil. Each of the activities are in place to perform different function and involved different facility. In such high technological supply chain, risk assessment process is in place from top down to assess technological risks that embedded in each activity to minimize technological disaster incident, asset damage and losses of human life occur. The study of technological risk assessment process in supply chain is considerable as new and under-study kind of research. This is because, the existing risk assessment process are only in place to provide high level of guideline. The process to assess technological risks on each supply chain activities are still unknown. Therefore, it is time to establish a technological risk assessment process framework that provide technological risk assessment process and assess technological risks factors along crude oil supply chain activities. The research was based on interpretivism paradigms under an exploratory study. This research is focused on identifying the factors of technological risks that embedded on each activity and technological risk assessment process that can adopted by each similar high technological risk supply chain activity. By knowing the factor of technological risk and risk assessment process, root cause of technological risk can be identified and assessed. Therefore, this research gives a new vision on risk assessment process that can be used to assess technological risks. Single case study and in-depth literature review were employed as the research design approach. Two key data collection methods (qualitative methods) were used: Primary data from face-to-face interview with PETRONAS. Secondary data from official documents. Also, one methods of analysis were used, namely: Explanation building. The literature review on supply chain, supply chain risks, technological risks and risk assessment identifies the need of understanding the results of technological risk assessment process on supply chain activity, technological risk categorize and the risk assessment process. Review on the previous study allows the researcher to establish the theoretical framework. The case study analysis led to the identification on the real practices of high technological risk industry that embedded technological risk across the supply chain activity. Thus, the researcher gained the information on technological risk assessment process and also the technological risk factors that embedded on each activity. As a result, this study identified four technological risk factors on each supply chain activities and technological risk assessment process for each activity from case study. In turn, this research further underlines and suggested the framework of technological risk assessment process to assess technological risks across supply chain activities.